The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.toxlet.2018.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the nigrostriatal dopamine system after acute systemic PhIP exposure

Abstract: Heterocyclic amines (HCAs) are primarily formed during cooking of meat at high temperature. HCAs have been extensively studied as mutagens and possible carcinogens. Emerging data suggest that HCAs are neurotoxic and may be relevant to Parkinson's disease (PD) etiology. However, the majority of HCAs have not been evaluated for in vivo neurotoxicity. Here, we investigated acute in vivo neurotoxicity of 2-amino-1-methyl-6-phenylimidazo[4,5-b]pyridine (PhIP). PhIP is the most prevalent genotoxin in many types of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 71 publications
0
28
1
Order By: Relevance
“…Neurochemical analysis was performed similarly to described in previous studies [ 59 , 60 ]. Briefly, frozen brain samples were sonicated in 0.5 mL of 0.4 N perchloric acid (HClO 4 ) on ice.…”
Section: Methodsmentioning
confidence: 99%
“…Neurochemical analysis was performed similarly to described in previous studies [ 59 , 60 ]. Briefly, frozen brain samples were sonicated in 0.5 mL of 0.4 N perchloric acid (HClO 4 ) on ice.…”
Section: Methodsmentioning
confidence: 99%
“…These products can participate in a Maillard reaction to generate heterocyclic aromatic amines (HAAs) [ 9 ] and advanced glycation end products (AGEs). It has been reported that high HAA intake is associated with a variety of acute diseases, such as nonalcoholic fatty liver disease and neuronal damage [ 10 , 11 ]. Excessive intake of AGE will result in their accumulation in the human body.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we quantified 3-nitrotyrosine (3-NT), a byproduct of tyrosine nitration and an established marker of nitrosative stress. Previously, we reported that exposure to HAAs increased intracellular 3-NT levels in primary mesencephalic neurons and in rat brain (Agim and Cannon, 2018;Cruz-Hernandez et al, 2018;Griggs et al, 2014;Lee et al, 2015). Briefly, cells were plated on glass coverslips coated with poly-D-lysine (PDL) in a 24-well cell culture plate.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, HAAs across 3 subclasses (aminoimidazoaazarenes, a-carbolines, and b-carbolines) are toxic to dopaminergic neurons with varying potency (Cruz-Hernandez et al, 2018). Furthermore, a systemic in vivo study in rats showed that PhIP selectively affects dopaminergic neurotransmission and produces heightened oxidative damage specifically in nigral dopaminergic neurons (Agim and Cannon, 2018). Although the results from this in vivo study further underscore potential PD relevance, the requirement for high doses (100-200 mg/kg) relative to actual exposures and a lack of an overt lesion to the nigrostriatal dopamine system raise questions about translational differences between PD models and human patients Cannon, 2015, 2018).…”
mentioning
confidence: 99%